2015
DOI: 10.1161/circep.114.002296
|View full text |Cite
|
Sign up to set email alerts
|

Small Conductance Calcium-Activated Potassium Current Is Important in Transmural Repolarization of Failing Human Ventricles

Abstract: Background The transmural distribution of apamin-sensitive small conductance Ca2+-activated K+ (SK) current (IKAS) in failing human ventricles remains unclear. Methods and Results We optically mapped left ventricular wedge preparations from 12 failing native hearts and 2 rejected cardiac allografts explanted during transplant surgery. We determined transmural action potential duration (APD) before and after 100 nM apamin administration in all wedges and after sequential administration of apamin, chromanol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
(40 reference statements)
0
24
0
1
Order By: Relevance
“…These findings shed light on the underlying mechanisms of cardiac alternans, especially for failing hearts since I SK was shown to be up‐regulated in ventricular myocytes in heart failure (Yu et al . ). In this study, we used a ventricular AP model.…”
Section: Discussionmentioning
confidence: 97%
“…These findings shed light on the underlying mechanisms of cardiac alternans, especially for failing hearts since I SK was shown to be up‐regulated in ventricular myocytes in heart failure (Yu et al . ). In this study, we used a ventricular AP model.…”
Section: Discussionmentioning
confidence: 97%
“…6 With each new study on SK channels, their importance is further demonstrated in arrhythmia vulnerability in both the atria 7 and ventricles. 8 Apamin is a specific blocker of SK currents, and apamin sensitive SK currents ( I KAS ) have been shown to be heterogeneously upregulated within the heart failure substrate in both human studies with transplant hearts, 9, 10 and in animal models of heart failure. 11, 12 This heterogeneity has been observed both transmurally and on the same surface.…”
Section: Introductionmentioning
confidence: 99%
“…Large variations of I KAS densities have also been observed in VMs 8, 15, 35. The mechanisms by which some cells had more I KAS than others remain unclear.…”
Section: Discussionmentioning
confidence: 99%